Technological Innovation and Inclusive Growth in Germany - Wim Naudé; Paula Nagler (Institute of Labor Economics (IZA), 2017)
Technological innovation has historically contributed to inclusive economic growth in Germany. In more recent decades, however, this contribution has weakened due to the declining impact of technological innovation on labor productivity growth. Fearing that this declining impact would undermine the international competitiveness of the economy, real labor compensation was progressively curbed since the mid-1990s. This occurred inter alia through the government's erosion of the social welfare state, as well as through offshoring and reduced fixed capital investment of the corporate sector. The outcome was rising income and wealth inequalities. Between the mid-1990s and 2010 the rise in wage inequality was faster in Germany than in the United States, the United Kingdom, and Canada. To restore inclusive growth, two broad policy measures are recommended: first, to have appropriate compensatory social welfare policies in place; and second, to improve the effectiveness of technological innovation to raise labor productivity. This paper identifies three reasons why technological innovation has become less and less effective:(i) historical legacies, (ii) weaknesses in the education system, and (iii) entrepreneurial stagnation. Improving the impact of technological innovations on labor productivity growth will require a more diversified education system, a deepening of active labor market policies, better immigration policies, and a greater contestability of markets. Ensuring these recommendations in a coordinated fashion suggests the need for an appropriate industrial-innovation policy.
Keywords: D31; L26; O33; O38; O52; 330; entrepreneurship; Germany; inequality; innovation; social protection; technology